PERLINDUNGAN HUKUM TERHADAP ANAK HASIL ADOBSI DITINJAU DARI UU NO. 39 TAHUN 1999 TENTANG HAM DAN UU NO. 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK DI KOTA SAMARINDA - Umi Laili (Prodi Ilmu Administrasi Negara, 2015)
Unity state Republic Of Indonesia guarantee prosperity every its citizen, including protection to children right representing human right. Child is trust at the same time God Single grant from above The most, which ever we have to take care of because in coherent x'self of standing, prestige, and its rights as human being which must hold high is high. Than side life of and nation have state, child is nation future and of gerasi router dream of nation, so that each; every child is entitled to to the continuity of life, grow, and expand, participating and also is entitled to of protection from acting discrimination and hardness. Lifting of child (adobsi) is an deed of intake of others child into family alone, so that between old fellow collecting the collecting child and child arise an is same familiarity law, like old fellow and child with child contain alone him. Lifting of child can only be done/conducted by for the sake of best to child and conducted pursuant to local habit and rule of law and regulation going into effect. This Pelitian is done by using empirical method and have the character of quantitative join among and yuridis of normative about process punish and applying in child adoption. Then comparing them with child rights which is contained in Law about Human rights and Law Protection of Child and regulation of lagislation of other lagislations. Result of research indicate that lifting of town child of Samarinda in general is in fact executed to utilize to petrify all husband/wife spouse which not yet owned child and at the same time give aid to child coming family unable to, what is in general conducted with intention of good utilize is giving each other aid one another. But in its its his without procedure matching with law and regulation going into effect. Execution of lifting of child is that way resulted by its minim of knowledge of them to child rights in realizing protection of child.In order that children right to be able to live, grow, expanding, and participating in an optimal fashion hence to child which in adobsi is entitled to get foster parent or sponsor pursuant to justice decision if both old fellow have passed away or because of valid cannot do duty them as a is old. Lifting of child pursuant to law and regulation will give rule of law to society.